7x + 4 -2x - 8 =

(2x - 8) - (4x +8) =

5a(3+a) -4(2a- 3a^2) =

(-8b^2+10b-5) : 5

(3y - 4) (5-4y)=

5a(4b-6) - (4-a) (2b-3) =


Odpowiedź :

Hej!

7x + 4 - 2x - 8 = 5x - 4

(2x - 8) - (4x + 8) = 2x - 8 - 4x - 8 =

= -2x - 16

5a(3 + a) - 4(2a - 3a²) =

= 15a + 5a² - 8a + 12a² = 17a² + 7a

(-8b² + 10b - 5) : 5 = -1,6b² + 2b - 1

(3y - 4)(5 - 4y) = 15y - 12y² - 20 + 16y =

= -12y² + 31y - 20

5a(4b - 6) - (4 - a)(2b - 3) =

= 20ab - 30a - (8b - 12 - 2ab + 3a) =

= 20ab - 30a - 8b + 12 + 2ab - 3a =

= 22ab - 33a - 8b + 12